2017
DOI: 10.1155/2017/3657812
|View full text |Cite
|
Sign up to set email alerts
|

Everolimus Implicated in Case of Severe Gastrointestinal Hemorrhage

Abstract: Breast cancer remains the leading cause of cancer and the third leading cause of cancer related deaths among our population with an estimated number of 246,660 new cases and 40,450 deaths in 2016. With treatment advancements, including targeted agents such as Everolimus, a mammalian target of rapamycin (mTOR) inhibitor, survivability and quality of life continue to improve. However, with the use of these agents come adverse effects, some of which are still being characterized. Our case demonstrates recurrent e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…A) bleeding antral angiodysplasias that were treated with argon plasma coagulation (everolimus 3.5 mg/ daily); B) gastric antral bleeding erosions in a context of hyperemic and fragile mucosa (everolimus 4 mg/daily); C) endoscopic appearance 1 week after everolimus discontinuation. it presented as hemorrhagic colitis, while in the only case reported in a LT patient no definite source of bleeding was identified after repeated lower and upper GI tract endoscopic examinations [6][7][8][9][10] . Our patient presented for the first time, even considering his pre-LT clinical history, with GI bleeding that was initially interpreted as multifactorial: he was on prophylactic antiplatelet therapy with ASA and initially had concomitant endoscopic findings of gastric and colic angiodysplasia, all of them endoscopically apparently non-bleeding in the investigations performed after the first episode of melena and anemia.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…A) bleeding antral angiodysplasias that were treated with argon plasma coagulation (everolimus 3.5 mg/ daily); B) gastric antral bleeding erosions in a context of hyperemic and fragile mucosa (everolimus 4 mg/daily); C) endoscopic appearance 1 week after everolimus discontinuation. it presented as hemorrhagic colitis, while in the only case reported in a LT patient no definite source of bleeding was identified after repeated lower and upper GI tract endoscopic examinations [6][7][8][9][10] . Our patient presented for the first time, even considering his pre-LT clinical history, with GI bleeding that was initially interpreted as multifactorial: he was on prophylactic antiplatelet therapy with ASA and initially had concomitant endoscopic findings of gastric and colic angiodysplasia, all of them endoscopically apparently non-bleeding in the investigations performed after the first episode of melena and anemia.…”
Section: Discussionmentioning
confidence: 90%
“…Rare cases of severe hemorrhage have been reported in the literature during treatment with mTOR inhibitors, either everolimus or temsirolimus [6][7][8][9][10][11] . In five cases previously documented in the literature the patients were undergoing chemotherapy (2 cases for breast cancer, 2 cases for renal cancer, 1 case for metastatic neuroendocrine tumor), and in just one report the patient had previously undergone LT [6][7][8][9][10][11] . In four of the 5 cases bleeding originated from the upper digestive tract, and in one case Figure 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cases of severe gastrointestinal (GI) bleeding during targeted therapy with everolimus have been reported [2931]. In two of these reports, gastric antral vascular ectasia (GAVE) was identified as the likely cause of bleeding [29, 30]; GI bleeding was successfully treated with endoscopic hemostasis using argon plasma coagulation after treatment discontinuation.…”
Section: Methodsmentioning
confidence: 99%
“…In two of these reports, gastric antral vascular ectasia (GAVE) was identified as the likely cause of bleeding [29, 30]; GI bleeding was successfully treated with endoscopic hemostasis using argon plasma coagulation after treatment discontinuation. In another case, GI bleeding was associated with treatment initiation and resolved following discontinuation [31]. Endoscopy revealed that the bleeding was secondary to erosive gastritis, and several endoscopic interventions were needed to achieve hemostasis.…”
Section: Methodsmentioning
confidence: 99%